The effect of aqueous extract of white tea on serum levels of FSH, LH and testosterone in rats exposed to arsenic - Firoozeh Saberi Sis; Felor Zargari (Fasa University of Medical Sciences, 2017)
Background & Objective: Sodium arsenite is an environmental pollutants capable of generating free radicals causing oxidative stress. Oxidative stress is regarded as a major factor in male infertility by reducing sex hormone levels. The aim of this study was to investigate the antioxidant effect of white tea on serum levels of FSH, LH and testosterone in male rats exposed to arsenic.  Materials & Methods: In this experimental study, 32 adult male rats were randomly divided into four groups with eight rats in each. The first group was healthy rats (control group) that received distilled water with standard diet via gavage daily. The second group of rats was treated with 100 ppm sodium arsenite in drinking water, The third group of rats was treated with white tea (1.5%) and the fourth group received aqueous extract of white tea (1.5%) with arsenic (100 ppm in drinking water) via gavage. At the end of a 30-day time period, after providing serum, the enzyme-linked immunosorbent assay (ELISA), was used to analyze the hormones, and analysis of variance (ANOVA) and Duncan were applied to diagnose the differences. Results: The results showed that arsenic caused a significant decrease in FSH, LH and testosterone compared to the control group (p<0.05). Also, it was found that white tea extract with sodium arsenite significantly increased FSH, LH, and testosterone compared to the group that received arsenic (p<0.05).  Conclusion: It seems that the aqueous extract of white tea may be helpful in reducing the toxic effects of sodium arsenite on sex hormones.